Stress Levels and Coping Strategies Among Women Diagnosed with HIV During Pregnancy at Selected Health Facilities in Lusaka District, Zambia - Sianchapa, Brenda Nambala; Katowa-Mukwato, Patricia; Ngoma, Catherine M. (British Journal of Healthcare and Medical Research, 2023)
Background: In an effort to eliminate mother-to-child transmission of HIV, pregnant women undergo HIV testing during antenatal care. A diagnosis of HIV adds to the stress of pregnancy. When mothers diagnosed HIV positive during pregnancy utilize effective coping strategies, the stress levels decrease. Aim: To measure the levels of stress and categorise the coping strategies among women diagnosed with HIV during pregnancy. Methodology: An analytical longitudinal study design was used. Panel studies were used to collect data in 3 stages. Census sampling was done in selecting 110 study participants. The levels of stress were measured using the Perceived Stress scale adapted from Cohen, 1983, and the coping strategies were categorised using the Coping Strategy Indicator adapted from Armikhan, 1990. The Statistical Package for Social Sciences Version 26 was used to analyse data. Major findings: Majority of participants (57.3%, 65.6%, and 37.5%) had moderate levels of stress at stages 1, 2 and 3 of the study respectively. Majority utilised Problem focused (problem solving) coping (54.4 and 62.5%) at stages 2 and 3 of the study respectively. Kruskal-Wallis test indicated significant difference between the coping strategy used and the stress levels at stage 2 of the study [χ2 (2) = 23.708, p = .001]. Conclusion: The study recommends the use of the Perceived Stress Scale and Coping Strategy Indicator at every antenatal and postnatal visit for women diagnosed HIV positive during pregnancy, to identify those who are stressed and those who use maladaptive coping in order to assist them to cope.